2019
DOI: 10.14254/2071-789x.2019/12-2/13
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of project success factors: A cross-cultural comparison

Abstract: Project managers often run similar projects in a different way under the influence of particular factors. It is important to discover these factors, which may affect projects` success. The objectives of this study are to examine cultural differences in project running styles of three Asian countries with different level of economic development-Israel, Japan and Kazakhstan, and identify how their styles affect project success. The authors use PMPQ (Project Management Planning Quality) model for comparing the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…According to Anderson and Narus (1990), communication was the formal and informal spreading in a timely and appropriate way between communicators. As mentioned before, scholars regarded communication as an important predictor for project success (i.e., Wu et al 2017a;Forcada et al 2017;Lindhard and Larsen 2016;Kozhakhmetova et al 2019). What's more, Pinto, Slevin, and English (2009) had pointed out that meaningful communication between project partners was extremely important to project success, especially when construction projects were characterized by high level of uncertainty.…”
Section: Response: Communication and Coordinationmentioning
confidence: 99%
“…According to Anderson and Narus (1990), communication was the formal and informal spreading in a timely and appropriate way between communicators. As mentioned before, scholars regarded communication as an important predictor for project success (i.e., Wu et al 2017a;Forcada et al 2017;Lindhard and Larsen 2016;Kozhakhmetova et al 2019). What's more, Pinto, Slevin, and English (2009) had pointed out that meaningful communication between project partners was extremely important to project success, especially when construction projects were characterized by high level of uncertainty.…”
Section: Response: Communication and Coordinationmentioning
confidence: 99%
“…In addition to this industry, the analysis of the competitiveness and economic profit of Kazakhstan poultry companies and methods of commercialization of green technologies were considered [20,21].…”
Section: Formation Of a Logistics Services Subsystem And Customer Sermentioning
confidence: 99%
“…Turginbayeva et al (2018) considered financial issues of the effectiveness of innovative projects and evaluated the competitive advantages, based on the importance of increasing the region's competitiveness for the economy (Turginbayeva et al, 2013). Kozhakhmetova A et al (2019) found that differences in national culture influenced project management style and that project outcomes differed, which indicated that project success depends on project management style. Kunanbayeva In recent years, world tourism has been developing rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%